The magic finger - Dahl, Roald; Blake, Quentin (London : Puffin Books, 2016)
Suddenly a sort of flash comes out of me, like something electric. It jumps out and touches the Person who has made me cross...
Keywords: Magic -- Hunting stories -- Anger -- Fantasy -- Girls -- Hunters -- Hunting--Moral and ethical aspects -- Children's stories, English